A Smiling Face Is Half The Meal: The Role of Cooperation in Sustaining Maine’s Local Food Industry - Tremblay, Ethan; Waring, Timothy (Maine Policy Review, 2014)
The U.S. is experiencing a renaissance in local food production, and Maine is among the states leading that resurgence. This renaissance is influenced by many factors, and has both economic and social dimensions. This article examines the role of cooperation in the local food industry across a range of local food organizations. The authors conclude that cooperation plays different yet crucial roles in all local food organizations, and is an important part of the success of the local food industry as whole. The article considers the policy implications of these findings, and suggests that while the prevalence of cooperation is a healthy sign for a young industry, it does not guarantee the strength or longevity of the industry.